Islamic Education Curriculum Development - Sarwadi Sarwadi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The contents in the Islamic education curriculum are knowledge, experiences, and activities that are methodically imparted to pupils in order to help them reach their objectives. In addition, the curriculum is an activity that consists of detailed student activity plans in the form of instructional materials, ideas for teaching and learning tactics, program arrangements that allow them to be put into practice, and items that cover a range of activities up until the intended goals are met. The Al-Qur'an and the Hadith, which are the cornerstones of Islam, cannot be divorced from the Islamic Education Curriculum; so, its primary distinguishing feature is that it uses them as its primary sources. The curriculum for Islamic education must prioritize both subjects and religion.